IMPLEMENTASI PENDIDIKAN AGAMA ISLAM MELALUI PENYULUHAN UNTUK MENINGKATKAN RELIGIUSITAS ANAK NELAYAN : Potret PAI di Desa Mundupesisir Kecamatan Mundu Kabupaten Cirebon - Syafeie, Ahmad Khomaini; Nurihsan, Juntika; Syathori, Ahmad; Mahfud, Mahfud (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
ABSTRACT This article aims to ascertain/photograph and inform about the implementation of Islamic Religious Education for fishermen's children, the problems and solutions. This research was conducted in Mundu District, Cirebon Regency. The method used in this research is the counseling method with the following steps: First, make observations at the research location to see objective demographic and socio-economic conditions and the process of Islamic religious education; Second, holding interviews with leaders and residents: Third, doing reflection and Fourth, Socializing the constraints and solutions. The results of this research are that the implementation of Islamic religious education exists but is not optimal due to several constraints such as, a, family factors including limited parental religious knowledge, lack of parental attention due to busyness, fatigue, low economy and exemplary; b. child factor, lack of interest in learning Islam; and c. factors inadequate facilities and infrastructure. The countermeasures are making a study schedule, adjusting the desired learning atmosphere, providing support, repeating lessons at school, studying before going to bed, setting study time limits, studying children's learning types, accompanying children to study, giving rewards or awards, providing interesting books, learning while playing, teaching without emotion, using educational game media, explaining the benefits of learning and most importantly setting a good example (role model). Keywords: Religiosity, Islamic Religious Education, Counseling